UMPSA expands collaborative ties with 6 private schools in internationalisation of academic programmes - Nor Salwana, Mohammad Idris (UMPSA, 2025)
KUALA LUMPUR, 21 January 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has taken another step forward by establishing a strategic collaboration with six Chinese Private Secondary Schools through the signing of a memorandum of understanding (MoU) to enhance the university’s academic programmes.